Drawing a diagram of the triangle we have
Let a be the length of the perpendicular height of the triangle, then we can solve it using the Pythagorean Theorem
![\begin{gathered} a^2+b^2=c^2 \\ a^2+((2x+4)/(2))^2=(2x+1)^2 \\ a^2+(x+2)^2=(2x+1)^2 \\ a^2+x^2+4x+4=4x^2+4x+1 \\ a^2=4x^2+4x+1-x^2-4x-4 \\ a^2=3x^2-3 \\ √(a^2)=√(3x^2-3) \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mrwljk8onmr5vbjdf92rjethjnqr3cm3bd.png)
Therefore, the length of the perpendicular height of the triangle can be given in the expression
![√(3x^2-3)](https://img.qammunity.org/2023/formulas/mathematics/college/5vsvb6cjdvi6e4crtdcuofvxxwh2tq8nqb.png)